2017
DOI: 10.1016/j.pec.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

What is the problem with medically unexplained symptoms for GPs? A meta -synthesis of qualitative studies

Abstract: Please cite this article as: Johansen May-Lill, Risor Mette Bech.What is the problem with medically unexplained symptoms for GPs? A meta-synthesis of qualitative studies.Patient Education and Counseling http://dx.doi.org/10.1016/j.pec. 2016.11.015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 39 publications
(80 reference statements)
4
101
1
1
Order By: Relevance
“…Initially and in uncomplicated cases, an encompassing biopsychosocial attitude, a focus on symptomatic relief, patient activation, and avoidance of iatrogenic harm is particularly helpful. In more chronic and/or severe cases, management works best when not only the patients but also their doctors achieve a reframing of the clinical problem: from cure to care and coping, from classical biomedical explanations to a broader view of biologically and psychosocially aggravating and alleviating factors [79]. Importantly, this reframing from cure to care and coping is also necessary for mental health specialists and psychotherapists, as is the switch from classical psychosocial explanations to such a broader view of biopsychosocial modulators.…”
Section: Discussionmentioning
confidence: 99%
“…Initially and in uncomplicated cases, an encompassing biopsychosocial attitude, a focus on symptomatic relief, patient activation, and avoidance of iatrogenic harm is particularly helpful. In more chronic and/or severe cases, management works best when not only the patients but also their doctors achieve a reframing of the clinical problem: from cure to care and coping, from classical biomedical explanations to a broader view of biologically and psychosocially aggravating and alleviating factors [79]. Importantly, this reframing from cure to care and coping is also necessary for mental health specialists and psychotherapists, as is the switch from classical psychosocial explanations to such a broader view of biopsychosocial modulators.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may expand the uses of such insights to other professions and care settings and illustrate the powerful role played by medical imaginaries and frameworks in more settings than the clinic. Still experiencing conceptual incongruence (May et al, ) in relation to their explanatory models in these encounters, the professionals in our study invest in care alliances, or ‘relational congruence,’ to build a foundation for solving communicative dilemmas at later stages (Johansen & Risør, , p. 652).…”
Section: Discussionmentioning
confidence: 99%
“…A recurring theme in both medical and social research is clinicians’ dilemmas when attempting to understand, explain, and recognise suffering that is poorly expressed within a dominant reductionist biomedical framework and language (Jutel, ; Kirmayer, ). These dilemmas are illuminated in research on general practitioners (GPs) struggling to express psychosocial aspects and reconcile incongruent explanatory models with adult patients (Johansen & Risør, ; Van Ravenzwaaij et al, ). They are also reflected in research on clinical communication with youth (Buchbinder, ; Geist, Weinstein, Walker, & Campo, ; Hareide, Finset, & Wyller, ) showing negative perceptions attributed to psychosocial explanations.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Under current guidelines, GPs have a central position in the care of patients with MUS. [6][7][8] Though GPs agree that patients with MUS should be managed in primary care, many perceive these patients to be difficult, [9][10][11] with a dilemma over whether or not to pursue further diagnostic evaluations. GPs often feel pressurised to undertake or refer for further diagnostic testing, but studies show that it may be the GPs themselves and not the patients who initiate these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-synthesis of qualitative studies on management of patients with MUS in primary care identified 13 studies, all based on focus groups and interviews. 17 These studies mainly focused on explanations and relational aspects, and thus lacked information on GPs' actions with regard to stimulating symptom management. The few observational studies available focused on the topic of somatic interventions.…”
Section: Introductionmentioning
confidence: 99%